2008
DOI: 10.1038/nature06901
|View full text |Cite
|
Sign up to set email alerts
|

Draper-dependent glial phagocytic activity is mediated by Src and Syk family kinase signalling

Abstract: The cellular machinery promoting phagocytosis of corpses of apoptotic cells is well conserved from worms to mammals. An important component is the Caenorhabditis elegans engulfment receptor CED-1 (ref. 1) and its Drosophila orthologue, Draper 2 . The CED-1/Draper signalling pathway is also essential for the phagocytosis of other types of 'modified self' including necrotic cells 3 , developmentally pruned axons 4,5 and dendrites 6 , and axons undergoing Wallerian degeneration 7 . Here we show that Drosophila Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
206
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(215 citation statements)
references
References 30 publications
9
206
0
Order By: Relevance
“…The tyrosine kinases from our short list of candidates also have potential links to immunity. shark and Src42A are important for Draper-mediated glial phagocytosis of axonal debris (Ziegenfuss et al 2008) which, if left uncleared, stimulates an immune response, and Src64B overexpression has been shown to be sufficient for inducing an immune response in larva (Williams 2009). Even if Eya's threonine phosphatase activity is not involved, extending exploration of the interactions we have uncovered in the context of axon guidance to other biological contexts in which the candidate interacting partner is known to function may provide new insight into the cytoplasmic signaling networks in which Eya participates during development and disease.…”
Section: Resultsmentioning
confidence: 99%
“…The tyrosine kinases from our short list of candidates also have potential links to immunity. shark and Src42A are important for Draper-mediated glial phagocytosis of axonal debris (Ziegenfuss et al 2008) which, if left uncleared, stimulates an immune response, and Src64B overexpression has been shown to be sufficient for inducing an immune response in larva (Williams 2009). Even if Eya's threonine phosphatase activity is not involved, extending exploration of the interactions we have uncovered in the context of axon guidance to other biological contexts in which the candidate interacting partner is known to function may provide new insight into the cytoplasmic signaling networks in which Eya participates during development and disease.…”
Section: Resultsmentioning
confidence: 99%
“…However, we also showed that Siglec-11-expressing microglia have impaired capacity to phagocytose apoptotic neuronal material. Thus Siglec-11 signaling via ITIM might antagonize the phagocytosis-associated ITAM-Syk signaling pathways (Ziegenfuss et al, 2008). Consequently, higher neurite and neuronal cell body density in the cocultures with Siglec-11-expressing microglia might result either from less phagocytosis or reduced production of microglial proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Src42a phosphorylates an intracellular immunoreceptor tyrosinebased activation motif (ITAM) domain on Draper, the nonreceptor tyrosine kinase Shark then binds to the Draper ITAM, and engulfment is activated. 16 The phosphotyrosine-binding domain-containing protein dCed-6 also appears to signal downstream of the Draper receptor, 17 but additional signaling molecules that promote engulfment activity in glia remain poorly defined. Here we show that the Drosophila c-Jun amino-terminal kinase (dJNK) plays a critical role in glial responses to degenerating axonal debris.…”
mentioning
confidence: 99%